The Rate of Local Integration in the Supply Chain of a Car Manufacturer - Raissouni, Rajaa; Mhamed, Hamiche (Transactions on Engineering and Computing Sciences, 2017)
The rate of local integration is the share of production produced in Morocco in a context of production broken out around the world by multinationals When all the parts of an automobile are imported into Morocco and then assembled on the spot before being re-exported in the form of whole cars by a builder, then local integration comes down to assembly Local integration is a permanent challenge for Morocco's industrial policy. It is about bringing into the realm not a builder or two, but all their chain of subcontracting. "The challenge is to become the backbone of Europe for sourcing", and according to Renault Maroc, this sourcing "integrates local purchases and also export (excluding vehicles)". It is understood that the project aims to position Morocco as an exporter of automotive components of first rank. Moreover, the group is a VRP in Morocco since it has hosted 250 international suppliers in the Tangiers plant "to present the new ecosystem, the industrial platform of Tangiers, to encourage them to invest in our country." It is also learned that the local integration platform that will be created will include purchasing, engineering and logistics resources in order to optimize local sourcing and to make Morocco a solid industrial export base. In this article, we question the impact of local integration on the supply chain of Renault Morocco, which leads us to ask the following question : Does the increase in the local integration rate reduce the purchase costs of the multinational Renault? In this regard, we adopted a two-step approach: First we focused on the conceptual aspects of the purchasing function and the theoretical basis of sourcing. Secondly then presented a project for local integration and diagnosis of the body & Electrical perimeter applied within the company Renault Morocco.